Editorial: Special issue on learning design research: Mapping the terrain - Dobozy, Eva; Cameron, L. (ASCILITE, 2018)
© 2018 Australasian Journal of Educational Technology. Learning design as a field of educational research and practice is gaining traction internationally. Not only is learning design now acknowledged as a complex and integrated process, demanding specialised knowledge and skills, it is a field of technology enhanced learning and teaching that is forward looking and globally focused. This special issue is unable to provide a unified position of what learning design is or resolve the debate, but it is able to contribute to a better understanding of the complexity of this field of educational research and practice. It also showcases some of the cutting-edge work currently conducted internationally in learning design research and development.